Interventional endoscopic ultrasound: Therapeutic capability and potential - Tarantino, Ilaria (Baishideng Publishing Group Co., Limited, 2009)
The linear echoendoscope, introduced in the 1990s, opened the era of interventional endoscopic ultrasound (IEUS). The linear echoendoscope enabled EUS guided Fine Needle Aspiration (EUS-FNA) allowing the path of the needle to be traced during the puncture process. After EUS-FNA, other interventional procedures were introduced in clinical practice. Tissue acquisition was the first EUS-guided interventional procedure and its higher diagnostic quality has undoubtedly been established. After EUS-FNA, Celiac plexus neurolysis (CPN) and block (CPB), pancreatic pseudocyst drainage, abdominal and mediastinal collections/abscesses drainage, and in selected cases, pancreatic and biliary ductal system drainage, were introduced in clinical practice. EUS-guided fine needle injection with local delivery of antitumor agents is considered a promising modality. We have reviewed published data on EUS guided interventional procedures with the object of summarizing the diagnostic capability of endoscopic ultrasound and elaborates in detail its therapeutic capability and potential.